Evaluasi Switch Therapy Antibiotik pada Pasien Apendisitis di RSUP Dr. M. Djamil Padang - Sondang Khairani S.Farm., M.Farm., Apt (Jurnal Penelitian Farmasi Indonesia)
The way to optimize antibiotic therapy is to immediately replace intravenous therapy to oral (switch therapy). Intravenous antibiotic therapy must be switched to an oral preparation or stopped after 48-72 hours of injection, normal body temperature and normal white blood cell count. The purpose of this study is to evaluate antibiotic selection and timeliness for switch therapy. The sampling technique all patients hospitalized with appendicitis at surgical department Dr. M. Djamil Padang, from September until November 2013 received switch therapy, using a prospective observation study design with descriptive analysis. Results showed that 36 patients entered the inclusion criteria. All use ceftriaxone intravenous, for oral antibiotics cefixime 25 patients, ciprofloxacin 11 patients. There were 8 patients on time when switching intravenous antibiotic therapy to oral. Switch therapy antibiotic almost on the third day of treatment 67%. The 36 patients studied had returned in improved clinical improvement and doctor’s approval.